Analisis Struktur Modal Terhadap Profitabilitas (Studi Empis Subsektor Kosmetik Dan Keperluan Rumah Tangga Yang Terdaftar Di Bursa Efek Indonesia) - Fathimah Saputri, Maulidya; Nurlia, Nurlia; Juwari, Juwari (Jurnal GeoEkonomi, 2025)
This study focuses on the impact of capital structure on the level of profit in the cosmetics and family products sector listed on the IDX. Capital structure is explained through several financial indicators, such as the current ratio, debt to equity ratio, and debt to asset ratio, while profitability is presented by return on equity. The research uses multiple linear regression to analyze data by utilizing company financial reports during a certain period. The findings show that the current ratio does not make a significant contribution to return on equity, while the debt to equity ratio has a significant positive impact. On the other hand, the debt to asset ratio does not show a significant negative effect on return on equity. It is hoped that the results of this research can help company management in preparing capital structure strategies and serve as a guide for investors to strengthen the company's financial performance.